A real-time fluorescence turn-on assay for acetylcholinesterase activity based on the controlled release of a perylene probe from MnO2 nanosheets. Issue 19 (26th April 2017) - Zhang, Yunyi; Zhang, Cuiyun; Chen, Jian; Li, Yongxin; Yang, Meiding; Zhou, Huipeng; Shahzad, Sohail Anjum; Qi, Hong; Yu, Cong; Jiang, Shichun
Abstract : A real-time perylene probe fluorescence turn-on method for the detection of acetylcholinesterase (AChE) activity through the selective decomposition of MnO2 nanosheets. Abstract : We exploit a real-time perylene probe fluorescence turn-on method to detect acetylcholinesterase (AChE) activity through the selective decomposition of MnO2 nanosheets. The surface of the MnO2 nanosheets is negatively charged. The perylene probe (P -4C+) has four positively charged quaternary ammonium groups. When mixed together, P -4C+ attached to the surface of the MnO2 nanosheets through electrostatic attractive interactions. The fluorescence ofP -4C+ was effectively quenched by the MnO2 nanosheets. Acetylthiocholine (ATCh) could be hydrolyzed to thiocholine by AChE. Thiocholine is a reducing agent. It could reduce MnO2 nanosheets to Mn 2+ and thus trigger the decomposition of the MnO2 nanosheets. As a result, P -4C+ was released and the fluorescence ofP -4C+ was restored. The AChE inhibitor restrained the catalytic activity of AChE and resulted in a reduced fluorescence recovery ofP -4C+. Our assay method is simple and selective, with low toxicity and better biocompatibility, which would facilitate biological and biomedical applications associated with AChE activity.